2013
DOI: 10.1001/jamainternmed.2013.232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Providing Fee Data on Laboratory Test Ordering

Abstract: Inpatient care providers often order laboratory tests without any appreciation for the costs of the tests.Objective: To determine whether we could decrease the number of laboratory tests ordered by presenting providers with test fees at the time of order entry in a tertiary care hospital, without adding extra steps to the ordering process.Design: Controlled clinical trial.Setting: Tertiary care hospital.Participants: All providers, including physicians and nonphysicians, who ordered laboratory tests through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 27 publications
(29 reference statements)
4
149
0
1
Order By: Relevance
“…[23][24][25][26][27] Of the seventeen studies, seven were randomized controlled trials, 11,12,14,19,23,24,26 eight were pre-intervention vs. postintervention studies, 15,16,18,[20][21][22]25,27 and two had a concurrent control and intervention groups, but were not randomized. 13,17 Eleven studies examined physician ordering of laboratory or radiology testing, [11][12][13][14][15][16][17][18][19]23,24 while six looked at medication choice. [20][21][22][25][26][27] The details of the study design, study size, bias considerations, and follow-up period for the included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Of the seventeen studies, seven were randomized controlled trials, 11,12,14,19,23,24,26 eight were pre-intervention vs. postintervention studies, 15,16,18,[20][21][22]25,27 and two had a concurrent control and intervention groups, but were not randomized. 13,17 Eleven studies examined physician ordering of laboratory or radiology testing, [11][12][13][14][15][16][17][18][19]23,24 while six looked at medication choice. [20][21][22][25][26][27] The details of the study design, study size, bias considerations, and follow-up period for the included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…There were a total of nine papers in this category: four randomized controlled trials, 11,12,14,19 two non-randomized controlled trial, 13,17 and three pre-intervention vs. post-intervention studies 15,16,18 that looked at test ordering. Four interventions were conducted in inpatient wards [11][12][13][14] two were conducted in emergency department, 15,17 two were in intensive care units, 16,18 and one was in an internal medicine outpatient clinic. 19 Six were conducted in the United States 11,12,[14][15][16]19 ; studies were also conducted in South Africa, 13 Sweden, 17 and France.…”
Section: Interventions In a Clinical Settingmentioning
confidence: 99%
“…Two recent studies have demonstrated that displaying costs in the electronic order entry system reduced the ordering of lab tests. 31,32 Hospitals could improve the availability of, and potentially even require participation in, continuing medical education focused on cost-conscious care. Technology could be utilized to help disseminate best practices and educational materials from hospitals with demonstrated success in this area to institutions with fewer resources.…”
Section: Discussionmentioning
confidence: 99%
“…5,11,12 However, results from early attempts to encourage physicians to provide lower cost medications through decision support tools have had mixed success. A study by Ornstein et al 13 reported that providing medication cost information in the EHR of a family-practice clinic did not change the overall cost of medications prescribed.…”
Section: Introductionmentioning
confidence: 99%